Balancing the needs of policy and practice, while remaining authentic: an analysis of leadership and governance in three national school leadership colleges. (1st November 2018) - Greany, Toby
The contribution that school leadership can make to school and teacher quality – and thereby to pupil learning – is widely recognised. Pressures on school leaders have increased in recent years, as a result of increased accountability and higher expectations from policy as well as wider societal, economic and technological changes. In response, a number of school systems have established national leadership colleges with a remit to improve the supply and quality of leadership. This article analyses how such national colleges are established and operate in the context of wider system governance, with a focus on examples in England, Scotland and Singapore. It is informed by a review of literature and interviews with current and former chief executives (CEOs) of the three colleges. Critics argue that these national colleges represent a form of 'institutionalised governance' (Gunter and Forrester, 2009: 349), a mechanism for enacting hierarchical policy reforms through the creation of a willing cadre of officially approved front- line leaders. Alternatively, viewed through the lens of complexity theory (Burns and Koster, 2016), these colleges can be seen as a means to align policy and practice and to enhance system and professional learning. This article finds evidence to support both lines of argument, but also highlights differences between the three colleges, for example in their relationship with policy and in their operating models. For example, while Singapore's settled policy environment means that the director can focus on working productively with policy makers, the two UK CEOs must navigate more volatile policy landscapes, requiring them to engage more actively with both policy and practice at the same time. Balancing these demands can be difficult, and whilst there is some evidence that the colleges can support system alignment and improvement, they are subject to political demands and changes which can compromise their role and potential impact.